2007
DOI: 10.3844/ajassp.2007.565.569
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effects of Ramadan Fasting on the Serum Glucose and Lipid Profile among Healthy Jordanian Students

Abstract: Abstract:Ramadan is the holiest month in the Islamic calendar and Muslims fast during this month. We designed this study to evaluate the effect of Ramadan fasting on plasma lipids profile and serum glucose among healthy Jordanian students. Ramadan fasting entails major changes in sleep pattern, physical activity and eating habits, which may cause changes in metabolism both in health and disease. This cohort study was performed during Ramadan in October 2006 (Islamic year 1427). The subjects were 70 healthy Jor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 15 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…A study done in Jordan showed non-significant rise in triglyceride and Weight before(KG) blood glucose at end of fasting [19], which is also a non-significant finding in our study.…”
Section: Discussionmentioning
confidence: 29%
“…A study done in Jordan showed non-significant rise in triglyceride and Weight before(KG) blood glucose at end of fasting [19], which is also a non-significant finding in our study.…”
Section: Discussionmentioning
confidence: 29%
“…Ramadan fasting are provides an excellent opportunity to study the effects of the prolonged reduction of meal frequency on body metabolism. In this study, there was no significance difference between of cholesterol before and during fasting Ramadan (p=0.052).The previous also showed cholesterol increase in subjects during fasting Ramadan and there was no significance difference [5] [6].But some studies have reported there are decreases in total cholesterol during fasting Ramadan. [4] The changes are occurred probably due to the change of proportion and type fat intake of subjects.In the study subjects of 6 women and 5 men that the consumption of low fat diets induces a decrease of plasma cholesterol and accompanied with body weight reduction.…”
Section: Lipid Profile Differences Before and During Ramadan Fastingmentioning
confidence: 46%
“…Its also showed the significant reduction in LDL occurred regardless of the tendency of consume fried food that increase during Ramadan compared to before Ramadan. [12] Anthony (2005) [13] showed the LDL cholesterol were forms the fatty deposits in arterial wall and which become plaques that grow, rupture and stimulate the formation of artery blocking blood clots. This LDL a potential causative role in atherosclerosis and heart disease.…”
Section: Lipid Profile Differences Before and During Ramadan Fastingmentioning
confidence: 99%
“…Inclusion criteria were the males aged >22 years which married for more than one year, having normal sperm count (sperm count of ≥20×10 6 mL −1 ) (Engel et al, 1999;Mansi et al, 2007), none were taking an oral antioxidant supplement for three months prior to the study and their wives have not been pregnant from their marriage. Exclusion criteria were intercourse problems, chronic disease including diabetes mellitus, substance, alcohol or drug abuse, semen samples with more than 1×10 6 mL −1 neutrophils using peroxidase staining (World Health Organization WHO), 1999; Marjani et al, 2008) or other round cells and use of contraception methods within last year before presentation.…”
Section: Methodsmentioning
confidence: 99%
“…The most common method is ABTS-based method in which a colorless molecule, reduced ABTS, is oxidized to a blue-green ABTS. When the colored ABTS is mixed with any substrate that can be oxidized, it is reduced to its original colorless form again (Erel, 2004;Mansi et al, 2007).…”
Section: Measurement Of Tac Levelsmentioning
confidence: 99%